Cerasus avium L.(kiraz) ve Cerasus vulgaris Miller (vişne) polenlerinin çimlenmesi ve tüp büyümesi üzerine asitliğin etkileri - Topdemir, Aykut; Gür, Nazmi; Topdemir, Gülşah (My University, 2012)
The aim of this study is to investigate effects of acidity on in vitro polen germination and tube length of Cerasus avium L. and Cerasus vulgaris Miller plants.Pollens of Cerasus avium L. and Cerasus vulgaris Miller flowers have been exposed different concentrations of acid solutions in range of pHs 6.0 to 2.8. Brawbaker Kwack medium was used for pollen germination. According to the results obtained, germination rate and pollen tube length for each plant at least has been affected at pH 6.0. Pollen germination and tube length decreased high rate with increasing acidity . The decrease rate were calculated % 97.98 for pollen germination and % 99.11 for tube length of Cerasus avium L.; %98.77 for pollen germination and %96.31 for tube length of Cerasus vulgaris Miller at pH 2.8.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Asitlik; Cerasus avium L.; Cerasus vulgaris; Polen çimlenmesi; Polen tüpü gelişimi